1991
DOI: 10.1055/s-2007-1024730
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute Moderate Exercise on Serum Lipids and Lipoproteins in Mildly Obese Women

Abstract: The extent and duration of serum lipid and lipoprotein changes were examined in 12 mildly obese women who walked 45 minutes at 60% VO2max in a laboratory setting. A two-factor, 2 x 6 design with repeated measures on both factors was utilized. The first factor was condition (exercise and rest) and the second factor was time (six times of measurement over a 24-hour period) with treatment counterbalanced. The patterns of change in total high-density lipoprotein-cholesterol (HDL-C) [F(5,55) = 5.75, p less than 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 15 publications
(52 reference statements)
1
23
0
2
Order By: Relevance
“…Thus, as performed in the studies discussed below, changes that occur during postexercise recovery can be compared to changes that may occur on sedentary occasions. There appear to be no significant changes in total cholesterol (TC) or low-density lipoprotein cholesterol (LDL-C) in either sex during the hours following a single exercise session (Gill et al 2003; Gordon et al 1996; Lee et al 1991), but results for TG and HDL-C are somewhat more promising. In women, following an acute exercise bout, it was reported that plasma TG concentration declined within 90 min after exercise (Lee et al 1991) and the effect was sustained until the following day (Gill et al 2003; Lee et al 1991), though others did not find TG to be depressed on the day after exercise (Magkos et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as performed in the studies discussed below, changes that occur during postexercise recovery can be compared to changes that may occur on sedentary occasions. There appear to be no significant changes in total cholesterol (TC) or low-density lipoprotein cholesterol (LDL-C) in either sex during the hours following a single exercise session (Gill et al 2003; Gordon et al 1996; Lee et al 1991), but results for TG and HDL-C are somewhat more promising. In women, following an acute exercise bout, it was reported that plasma TG concentration declined within 90 min after exercise (Lee et al 1991) and the effect was sustained until the following day (Gill et al 2003; Lee et al 1991), though others did not find TG to be depressed on the day after exercise (Magkos et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, only men have demonstrated an increase in HDL-C after performing a single bout of aerobic exercise expending between 350 and 500 kcal Grandjean et al 2000). In contrast, lean, premenopausal women that performed a single exercise session requiring 500 kcal or less of energy expenditure have not been observed to increase the concentration of HDL-C at 24 or 48 h postexercise (Lee et al 1991;Pronk et al 1995;Imamura et al 2000;Wooten et al 2008). It remains unclear as to why triglyceride and HDL-C concentrations were not modified following the exercise session; however, it is recommended that future studies include enzymatic measurements (i.e., lipoprotein lipase, hepatic lipase, cholesteryl ester transfer protein, and lecithin:cholesteryl acyl transferase) to determine if lipoprotein-associated enzymes were similarly unresponsive.…”
Section: Discussionmentioning
confidence: 76%
“…To date, several studies have been conducted to determine the effects of a single bout of aerobic exercise in premenopausal women (Lee et al 1991;Pronk et al 1995;Gordon et al 1998;Imamura et al 2000;Wooten et al 2008); however, none of these studies have examined the responses in sedentary, obese women. In only 3 of these previous investigations were the participants sedentary (Pronk et al 1995 in the other investigations the participants were either trained (Gordon et al 1998) or had participated in an exercise program prior to the acute exercise trial (Lee et al 1991). The present data provides evidence that a single session of moderate-intensity aerobic exercise expending 500 kcal of energy was insufficient to modify lipid and lipoprotein-cholesterol concentrations, as well as the electrophoretic characteristics of lipoproteins in this group of normolipidemic, obese women.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One study evaluated the acute effects of exercise on serum lipids and lipoproteins in women. Lee et al [25] reported that relative to the baseline and rest condition, HDL cholesterol tended to rise postexercise, with values returning to baseline 1.5 hours postexercise. This increase was due to an increase in HDL 3 cholesterol rather than HDL 2 cholesterol.…”
Section: Effects Of Physical Activity On Risk Factorsmentioning
confidence: 96%